MANAJEMEN SUPERVISI AKADEMIK KEPALA SEKOLAH DAN PERAN KOMITE SEKOLAH TERHADAP KINERJA GURU - ELVI MARFINDA (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
Talking about education will not be separated from the term quality. The quality indicator itself can be measured by supervision activities that can be carried out by the principal as the head of the institution and the school committee as an agency that accommodates the aspirations of the community regarding improving the quality of education. The role of the principal and the school committee should be able to make a breakthrough in terms of managing teacher performance. The research chosen by the author is library research, namely research that utilizes library resources by tracing and reviewing primary and secondary literatures, books on academic supervision, the role of school principals and school committees, building a climate of collaboration and other scientific writings. The success of principals and school committees in improving teacher performance is very dependent on the management of supervision carried out including the stages of preparation, implementation, evaluation and follow-up. The ability of the principal to build a good climate of cooperation with the school committee will make it easier for his institution to achieve common policies and goals in terms of controlling the quality of education in his institution on an ongoing basis. This article aims to describe the management of school principals' academic supervision and to analyze the role of principals and school committees in improving teacher performance. ABSTRAKBerbicara pendidikan tidak akan lepas dengan istilah mutu. Indikator mutu itu sendiri dapat diukur dengan kegiatan supervisi yang dapat dilakukan oleh kepala sekolah sebagai pimpinan lembaga dan komite sekolah sebagai badan yang mewadahi aspirasi masyarakat terkait peningkatan mutu pendidikan. Peran kepala Sekolah dan komite sekolah seyogyanya mampu melakukan terobosan dalam hal pengelolaan kinerja guru. Penelitian yang dipilih penulis merupakan penelitian kepustakaan atau library research yaitu penelitian yang memanfaatkan sumber pustaka yang dilakukan dengan cara menelusuri dan menelaah literatur-literatur primer maupun sekunder buku-buku tentang supervisi akademik, peran kepala sekolah dan komite sekolah, membangun iklim kerjasama serta karangan ilmiah lainnya. Keberhasilan kepala sekolah dan komite sekolah dalam peningkatan kinerja guru sangat bergantung dari manajemen pengawasan yang dilakukan meliputi tahapan persiapan, pelaksanaan, evaluasi dan tindak lanjut. Kemampuan kepala sekolah membangun iklim kerjasama yang baik dengan komite sekolah akan memudahkan lembaganya mencapai kebijakan dan tujuan bersama dalam hal mengontrol mutu pendidikan di lembaganya secara berkesinambungan. Artikel ini memiliki tujuan untuk mendeskripsikan manajemen supervisi akademik kepala sekolah dan menganalisis peran kepala sekolah dan komite sekolah dalam peningkatan kinerja guru.